Validation of the Persian Involuntary Musical Imagery Scale alongside multifaceted investigation of earworms among Iranian college students - Tabahori, Aref; Bigdeli, Imanollah; Kareshki, Hossein (Frontiers in Psychology, 2025)
IntroductionInvoluntary musical imagery is considered a ubiquitous phenomenon worldwide, while mixed and inconsistent results regarding different aspects of earworms remain challenging. Furthermore, there is a special need for research on earworms in societies other than in European or American. The primary aim of our study is to validate the Persian Involuntary Musical Imagery Scale (PIMIS) and, secondly, to carry out a detailed exploration of earworms among Iranian college students.MethodsA total of 946 Iranian college students were recruited to answer the Persian Involuntary Musical Imagery Scale (PIMIS), and gold standards including the Thought Control Questionnaire (TCQ, to convergent validity), the Depression, Anxiety, and Stress Scale (DASS-21, to concurrent validity), the White Bear Suppression Inventory (WBSI, to predictive validity), as well as the NEO Five-Factor Inventory (NEO-FFI), the Obsessive-Compulsive Inventory-revised (OCI-R), and socio-demographic queries. A complex of features regarding the validity and reliability of the PIMIS, along with numerous aspects of earworm, were explored.Results and discussionThe Persian Involuntary Musical Imagery Scale encompasses 15 items along with three additional questions. It was found to be a valid and reliable instrument among Iranian college students, qualified to measure individual differences in earworms. Phenomenological evidence and detailed data on individual differences could provide rich knowledge for the rest of the literature paradigms. Moreover, future investigations into the local regions of the Iranian population are recommended.